Blood Pressure Monitor Design Using MPX5050GP Pressure Sensor and Visual C# 2010 Express: Ayu Jati Puspitasari, Endarko Endarko, Iim Fatimah - Ayu Jati Puspitasari Ayu Jati Puspitasari; Endarko Endarko; Iim Fatimah Iim Fatimah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
Blood pressure monitor (BPM) using oscillometric method with MPX5050GP pressure sensor has been successfully fabricated and calibrated. Oscillometric method is measurement method to observe cuff pressure oscillations. In this study, the oscillometric waveform measured by fabricated BPM used Arduino Uno which processes pulse rate, systolic and diastolic pressures. Measurement results of pulse rate, systolic and diastolic pressures will be displayed and recorded in application designed using Visual C# 2010 Express. Fabricated BPM capable of measuring pulse rate and blood pressure in the range of 40-260 mmHg with ratio of systolic and diastolic pressures were achieved 0.48 and 0.78, respectively. The system has an average error of systolic pressure, diastolic pressure, and pulse rate were -4.38 mmHg (2.72%), 0.10 mmHg (5,55%), and 4.48 bpm (6.07%).